Nutritional status of the adolescent mothers in a rural area of Bangladesh - Begum, Masuma; Mehedi, Md Tarique; Mahmud, Arif; Riya, Sayeda; Rahman, Kazi Monisur (Journal of Dhaka Medical College, 2013)
Background: Adolescence is a significant period of human growth and maturation. In Bangladesh adolescent population is about 24% and highest prevalence of nutritional deficiencies occur during adolescence. The young mothers nutritional status is very important. This cross-sectional study was carried out to investigate the nutritional status and dietary pattern of adolescent mothers. Methods: Total 103 adolescent mothers nutritional status was assessed by anthropometric measurements-height, weight, MAC and BMI. Food intake pattern was assessed by food frequency questionnaire and nutrient intake was assessed by 24 hours recall method. Results: Underweight was 39.8%, normal weight 51.5% and overweight 7.8%. Mean calorie intake was 1838.38 Kcal (81.34% of RDA), daily protein intake was 58.74 gm (124.98% of RDA) and daily fat intake was 58.75 gm (117.75% of RDA). about 57.31% of the total calorie intake (1789.19 Kcal) came from carbohydrate source, 13.13% from protein and 29.55% from fat. A significant percentage of mothers did not take milk (25.5%) or egg (22.5%) once in a week. Pulse was consumed regularly above 6 times a week by 54.9% of the mothers. Fish was consumed 4-6 times by 39.2%, green leafy vegetables above 6 times by 35.3%. There were positive association found between nutritional status and family size, monthly family income and total calorie intake. Conclusion: nutritional status of the adolescent mothers were not so satisfactory. nutritional status is largely associated with their socio-economic status and family size. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15539 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 7-10